2015
DOI: 10.1590/s1516-89132015060255
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cu, Fe, Mn, and Zn in Two Mangroves of Southern Brazil

Abstract: This study assessed the relation between Cu, Fe, Mn, and Zn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
1
Order By: Relevance
“…Brazil (Madi et al 2015), or in Indonesia (Martuti et al 2016). It was reported that the Cu partitioning in sediments of the Can Gio mangrove was mainly related to sulphide precipitation and to its complexes with organic compounds (Thanh-Nho et al 2019).…”
mentioning
confidence: 99%
“…Brazil (Madi et al 2015), or in Indonesia (Martuti et al 2016). It was reported that the Cu partitioning in sediments of the Can Gio mangrove was mainly related to sulphide precipitation and to its complexes with organic compounds (Thanh-Nho et al 2019).…”
mentioning
confidence: 99%
“…Mn concentration in all mangrove and halophytes was far more than the suggested level of 20 ppm (Underwood 1981), particularly, Sonneratia apetala leaves showed significantly high (P<0.05) concentration of Mn (934.95 ppm) among all the recorded plants. Significant correlation between soil and leaf micronutrients was earlier reported by Madi et al (2015). Therefore higher levels of micronutrients in leaf samples might be attributed to higher micro-nutrient concentration in soil.…”
mentioning
confidence: 54%
“…These two sites (HB and CO) of Paranaguá bay are known to be impacted by harbor activities and human occupation (Sá et al, 2006;Choueri et al, 2009;Santos et al, 2009;Martins et al, 2010;Santos et al, 2014). The reference site (RF) is on the Guaratuba bay, a remarkably non-impacted bay, as described by several recent studies (Combi et al, 2013, Rodrigues et al, 2013, Madi et al, 2015, Prodócimo et al, 2015. We transported the fish to a research station right after the sampling, and obtained the total weight (TW) and length (TL).…”
Section: Fish Samplingmentioning
confidence: 99%
“…Guaratuba bay, used in this study as reference site, is a touristic area and commonly known for low-scale fishing, angling, banana and citrus cultivation, and mariculture (Mizerkowski et al, 2012). Even so, the levels of contamination found are acceptable for the activities aforementioned (Combi et al, 2013;Rodrigues et al, 2013;Madi et al, 2015;Prodócimo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%